CovidArchemyth and Pakistani Social Media Discourse - Fauzia Janjua; Syeda Aniqah Sabahat; Sara Anwar; Sehrish Aslam (Linguistics and Literature Review, 2020)
The 21st-century world has seen several natural calamities in the form of widespread diseases such as SARS outbreak (2002-2004), swine flu pandemic (2009), and now the Covid-19.  The outbreak of coronavirus has put the world in a state of anxiety and fear. As a result, a considerable social myths content has been disembarked as a dynamic response to the pandemic. Like elsewhere, the social media discourse on Covid-19 myths is being constructed and consumed in Pakistan. Considering Bouchard's concept of configuration of social myths as either "strictly contextualized" or having "universal features with loose ties to social mechanism," the investigation of the configuration of social myths of Covid-19 in Pakistani social media is explored. Furthermore, the myths were analyzed for co-relation and interconnectedness through intertextuality. The study propounds that the social media discourse of dominant social actors hailing from religious, social, and philosophical domains construe locally contextualized ideas of Covid-19. The social actors' coalition of all social myths set the scene for a Pakistani CovidArchemyth, which is intertwined with peculiarities of Pakistani tradition and culture.